Histopathological Analysis of the Product of Conception Following First Trimester Abortion; Is There a Diagnostic Value? - Tiwari, Archana; Karki, Asmita; Khanal, Anupa; Sapkota, Pratima (Journal of Nepalgunj Medical College, 2024)
Introduction: Abortion is one of the most common problems faced by women of reproductive age group in Nepal. The most common complication associated with abortion is Retained Product of Conception. Histopathology is the confirmatory diagnostic test for the confirmation of intrauterine pregnancy and associated gestational trophoblastic neoplasm. Aims: To evaluate the value of histopathological examination of products of conception in first trimester abortion. Methods: A hospital based descriptive cross sectional study conducted from June 2021 to May 2023, among the women admitted with diagnosis of first trimester abortion at Lumbini Medical College and Teaching Hospital. Results: Among 89 cases of abortions, incomplete abortion was the commonest type constituting 83.1% of the studied group. The majority of participants belonged to age group of 21-30 years (49.4%) with a mean age of 28.64±12.7 years. Histopathologic examination confirmed products of conception in 54 (60%) patients, partial molar pregnancy in 7 (7.86%) patients, decidual reaction in 4 (4.49%) patients, complete mole in 1 (1.12%) patient and hydropic abortus in 12 (13.48%) patients. Conclusion: The histopathological examination of the products of conception proved to be an important tool in confirming intrauterine pregnancy and to find out possible pathologies associated with product of uterine evacuation like molar pregnancy and hydropic changes that necessitate special follow-up and further management.